Analysis of Spatial Mismatch and Equity using Commuting and Labor Sheds: Trends in Indiana. Issue 10 (October 2019) - Chacon-Hurtado, Davis; Kumar, Indraneel; Gkritza, Konstantina; Fricker, Jon D.
Commuting patterns are spatial interactions that result from the location decisions of firms, households, and the availability of transportation. Empirical evidence shows that these patterns differ across income groups, reflecting different levels of access to economic opportunities, such as jobs and modes of transportation. Accounting for this variability is an important aspect of paradigms and policies that strive for fair and equitable distribution of benefits and dis-benefits of transportation projects. However, measurable and widely accepted measures that could assist in the assessment of this distribution of transportation impacts are limited. This paper proposes a measure of accessibility mismatch for various income groups based on a ratio between commuting and labor sheds derived from open-access observed data. The paper demonstrates this measure using a case study of counties in Indiana between 2005 and 2007. The results show significant differences in the accessibility ratio between high-, middle-, and low-income groups as well as across metropolitan, micropolitan, and non-core counties, a commonly used geographical classification. This accessibility ratio can be used to explain the differences between commuting patterns across socioeconomic groups and their occupations as well as the identification of areas of limited accessibility and job opportunities.